IMAGE AND VIDEO DEPRESSION CLASSIFICATION METHODS BASED ON DEEP LEARNING: A REVIEW - Deshmukh, Pratiksha; Patil, Harshali (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Depression is the main psychological disorder, and it is diagnosed using the psychiatric evaluation and self-assessment questionnaires. However, these approaches are inefficient as they only diagnose depression in its final stages. In order to overcome this issue, deep learning-based methods have gained popularity to diagnose the depression in the early stage by analyzing the text, image, video, and biomedical signals. In this paper, image and video depression classification methods are studied and analyzed based on deep learning. Initially, in this paper, steps are required in the image/video depression classification method based on deep learning explained. Followed by a recent study of the depression classification method based on the dataset, pre-processing method, deep learning method, expected outcome, and inference drawn from it. Finally, we have defined the open research challenges in order to enhance the depression classification methods using the metaheuristic algorithms.